A gênese da Escola Rotary: interlocuções entre o público e o privado - 1956/1971 - Marçal, Josiane Aparecida (2017)
This work is the result of a research whose main purpose is to present the discovery of the genesis of the 1st Grade Rotary State School between 1956 to 1971, taking into account the relationships established between the public and the private in this educational institution. Its specific objectives are to answer some questions related to the implementation of this school in the municipality of Ituiutaba that in the selected years was considered "Rice Capital", because it standed out in economic strength for its intensive production of this grain. Therefore, our purpose also was to understand and analyze the governmental educational guidelines present in the period in question; to analyze documents, newspapers and iconographic clippings related to the emergence of the Rotary School in the years 1956 to 1971; to understand and characterize the historical agents in this process and what mechanisms were made for their stay in school, as well as discuss how the time and space for their operation was organized; to discover the relevance of the school's implementation and its contribution to the population of the municipality; to identify how educational thinking circulated during the era in the categories disseminated through the International Rotary Club Institution; and to understand how the correlation/connection between the international organization and the Rotary School has taken place. The methodological procedure for the research was defined in five distinct phases: a visit to the 1st Grade Rotary State School for the collection of official documents and school iconography in the school archives; visit to the Cultural Foundation of Ituiutaba to read newspapers for the proposed period and to the Ituiutaba Town Hall to read the minutes of the City Council; visit to the Rotary Club of Ituiutaba to read the minutes of the period in question, Rotary journals and magazines; consultation with the IBGE to understand the official statistical data regarding the municipality and the State Public Archive; and survey of bibliographic references, presidential messages, Pedagogical Magazines and of teaching. The results showed that the public and private relations present in the genesis of the school prove that they do not always appear in the Brazilian history of education in the form of conflicts, but also of exchange and conviviality. This possibly evidenced the omission of the Brazilian State towards public education. Thus, we conclude that this research provided the disclosure regarding the situation of the public school instituted in the municipality of Ituiutaba in the selected historical period, especially regarding the genesis of the Rotary School. Having completed this work has expanded the corpus of knowledge about school institutions even more, by making a transnational movement that discussed the condition of the institutionalization of the public school, not only at the local, but also in regional and national level. In this transnational movement we also understand the connection between the Rotary Club of Ituiutaba and the International Rotary Club, thus reflecting its dynamics and the ideology implicit in the Rotary principles reflected in the Rotary School and in the Ituiutaban society by some categories.